2012
DOI: 10.3892/etm.2012.827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mouse nerve growth factor on the expression of glial fibrillary acidic protein in hippocampus of neonatal rats with hypoxic-ischemic brain damage

Abstract: The present study aimed to investigate the influence of mouse nerve growth factor (mNGF) on glial fibrillary acidic protein (GFAP) expression in neonatal rats with hypoxic-ischemic brain damage (HIBD). A total of 60 7-day-old neonatal rats were randomly divided into control, HIBD and mNGF groups (n=20). The rats in the mNGF group were injected intramuscularly with mNGF once a day for 5 days. Each group was randomly divided into a day 7 subgroup and a day 14 subgroup according to the time of sacrifice. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…4,5 The prevalence of HIBD is about 6 in 1000 survival births, and approximately 25% to 30% of survivals suffer from long-term sequela, and thus it is a major cause reducing the quality of life of children across the world. 6 Following neonatal HIBD, changes of synaptic functions and electrophysiological characteristics instantly occur in the hippocampal CA1 pyramidal cells. 7,8 The neurological impairments due to HIBD include cerebral palsy, epilepsy, mental retardation, or even psychiatric problems, and the patients commonly suffer from a lifelong disability and a higher susceptibility to epilepsy, occurring in 15% to 60% of the children with cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The prevalence of HIBD is about 6 in 1000 survival births, and approximately 25% to 30% of survivals suffer from long-term sequela, and thus it is a major cause reducing the quality of life of children across the world. 6 Following neonatal HIBD, changes of synaptic functions and electrophysiological characteristics instantly occur in the hippocampal CA1 pyramidal cells. 7,8 The neurological impairments due to HIBD include cerebral palsy, epilepsy, mental retardation, or even psychiatric problems, and the patients commonly suffer from a lifelong disability and a higher susceptibility to epilepsy, occurring in 15% to 60% of the children with cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal HIBD represents the brain injuries induced by the hypoxia‐ischemia (HI) following perinatal suffocation, including a temporary occlusion or a reduction of cerebral blood flow, and has the characteristics of abnormalities in the central nervous system (CNS) . The prevalence of HIBD is about 6 in 1000 survival births, and approximately 25% to 30% of survivals suffer from long‐term sequela, and thus it is a major cause reducing the quality of life of children across the world . Following neonatal HIBD, changes of synaptic functions and electrophysiological characteristics instantly occur in the hippocampal CA1 pyramidal cells .…”
Section: Introductionmentioning
confidence: 99%
“…In children with CP, the addition of acupuncture injections of mNGF to the rehabilitation treatment can more effectively reduce blood lactate levels and improve motor function [20]. A study by Yin et al found that the mNGF treatment at a dose of 20 ng/g/day significantly promoted hippocampal neurogenesis and inhibited neuronal apoptosis in newborn rats with hypoxic-ischemic brain injury [21]; however, whether mNGF suppresses neuronal apoptosis and alleviates ASD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic-ischemic brain damage (HIBD) in neonates is mainly caused by perinatal asphyxia, and its prevalence is about 1–6% ( 1 ). Nearly one-third of the survivors develop mental retardation, epilepsy, cerebral palsy, and other sequelae ( 2 ). Mild hypothermia is often used to treat HIBD; however, the clinical treatment of HIBD often misses its best therapeutic window and cannot significantly improve the prognosis of children with severe HIBD ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%